Characteristics of water containers influencing the presence of Aedes immatures in an ecotourism area of Bang Kachao Riverbend, Thailand - Pathavee Waewwab; Sungsit Sungvornyothin; Kamolnetr Okanurak; Ngamphol Soonthornworasiri; Rutcharin Potiwat; Chadchalerm Raksakoon (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to investigate the influence of breeding containers on the production of Aedes mosquitoes after a vector-control program in households that might support dengue transmission in tourist attraction areas of Bang Kachao Riverbend, Thailand. Design/methodology/approach - A cross-sectional study was conducted in an ecotourism area of Bang Kachao Riverbend, Thailand, during the period October 2016 to September 2017. A total of 832 households from five villages participated in the study. Data collection employed an interview questionnaire, larval mosquito survey and measurements of the chemical properties of the water in each container. A binary logistic regression model was used to investigate the characteristics of water containers influencing the presence or absence of Aedes immatures. Findings - The study found that water containers located inside households had a highly presence of Aedes immatures (2.22 times) compared with outdoor containers. Water containers without lids and water containers with ineffective had a high presence of Aedes immatures (3.69 and 2.54 times, respectively). In addition, the chemical properties of the water inside the containers, such as pH, influenced the presence of Aedes immatures (1.76 times) (OR=1.76, 95% CI=1.59-1.96). Originality/value - The study results emphasized the characteristics of water containers in households located in a tourist attraction area. The findings may inform public health vector-control messages for households located in the tourist attraction area.